Critical Evaluation of the Fibrin Plate Method for Estimating Fibrinolytic Enzymes and Activators - Auerswald, W; Doleschel, W (Thrombosis and Haemostasis, 1961)
1. Studies of the fibrinolytic effect of spontaneously activated plasmin preparations on normal and heated bovine fibrin plates showed that human plasmin preparations can be obtained, to which heated fibrin possesses a higher sensitivity than native fibrin.2. The results suggest that spontaneously activated human plasmin prepared from an euglobulin fraction is more or less accompanied by an agent which acts as activator for bovine plasminogen contained in native fibrin plates. It seems that this agent is identical to a serum factor which acts physiologically as plasminogen activator and is also responsible for the socalled “spontaneous activation”.3. The findings emphasize the necessity for standardizing testing procedures. Variations in processing the fibrinogen, variations in fibrinogen concentration, and especially in the duration of the heat treatment of the fibrin plates, may cause significant variations in the resulting sensitivity of the method which in turn may be reflected in diverging apparent activities.